#TITLE_ALTERNATIVE# - Bastian Manurung (NIM 10101052), Adolf
ABSTRACT: Robustness of control system to a tenuous of disturbance has been became a central issue in designing of control systems. One of control system that robust to disturbance is H2 control. This final project discusses H2 control theory and it is applied to suspension system such as mass-spring system, and hybrid vibration absorber system. The main purpose of designing of control system is to reduce vibration that happens to that system. The mathematics modeling will described and after that state space equation will described. Generalized plant can be obtained from plant and the weighting functions. Next, the optimal control is designed by using H2 control theory. From the simulation results, we can conclude.